THE USE OF GOOGLE FORM IN MAKING WRITING DESCRIPTIVE TEXT - Bella Ampow (Dialectical Literature and Educational Journal, 2021)
This research aims to produce development instruments and knowing the feasibility of development instrument by using google form application as a medium in the learning process of writing descriptive text in VII-A grade of SMP N 35 Bekasi. The research method that researcher use in is research and development (R&D). The data collection in this research is test and interview. The population in this research is all VII grade students of SMP N 35 Bekasi the number of students is 40 students. From this population, researcher took sample using random sampling. Thus, the sample in this research was obtained by VII-A grade students with a total of 13 men and 11 women. The overall test results showed good results i.e. obtained a very decent category with details: (1) Cronbach's Alpha reliability test obtained a .747, (2) Cohen's Kappa inter-rater reliability test (k) appraiser 1 and appraiser 2 obtained a valid result of 100% missing 0%. Based on the results of the reliability test feasibility, it can be concluded that learning media using google form application is very feasible to be used in the online learning process during pandemic covid-19 as a medium in making descriptive text writing in grade VII SMP N 35 Bekasi.